Cooperate while continuing to compete - Cámara de Diseño de Uruguay (Base Diseño e Innovación, 2018)
Thanks to the firm purpose of a group of design businessmen and state support, in the first decade of the 21st century an entity was born that has represented the discipline since then -not only in Uruguay- but worldwide.